Learning medieval and renaissance Latin in a new way - Boras, Damir (Array, 2006)
We present a new way of learning medieval and renaissance Latin using the portal that introduces the diachronic vocabulary of the Croatian and medieval and renaissance Latin, based on selected manuscript and printed dictionaries from the late 16th to the 18th century, using today's most advanced technology. Since these dictionaries are multi-lingual ones (all of them include Latin, and some dictionaries also include Italian, German and Hungarian), it is possible to explore the vocabularies of other languages as well. Our portal comprises following printed dictionaries: F. Vrančić's (1595), B. Kašić's (manuscript, 17th cent.), J. Habdelić’s (1670), LIBELLUS alphabeticus (1756). Learners of the medieval and renaissance Latin can also exploit the dictionary entry context and look at the original image of the entry as well. Some of the dictionaries already contain the translation to the modern Croatian, some of them are still in the translation process, and we also plan to include the translation to modern Latin for all of them. CRODIP (Croatian Old Dictionary portal) is a major resource for scholars of the Latin, linguistics, literature, history and culture of above mentioned languages. These dictionaries can be used as the powerful electronic resources for teaching Latin language that can be easily used in the classroom. The portal itself is a pioneer in the application of technology to old Croatian-Latin dictionaries.